Situation of children with special needs in the Philippines - Camara, Erlinda F. (1992)
This paper analyzes the situation of children with special needs including those with mental retardation, visual impairment, emotional disturbance, mental illness, social maladjustment, chronic illness, orthopedic handicap, and multiple impairments. Likewise it describes briefly national projects/services rendered on disability prevention and rehabilitation.
Keywords: Children with disabilities -- Care